Ação da radiação de alta energia nas propriedades mecânicas de compostos elastoméricos a base de SBR carregados com barita - Almeida, Jademir Jesus Pirapora de (2012)
In this work were studied the action of ionizing radiation on the physical-mechanical properties in elastomeric compounds based on styrene-butadiene rubber (SBR) filled with barite, opening way for application of these composites in the protection and shield against high-energy radiation, in the form of aprons. These aprons come to substitute the elastomeric ones with lead filler in ergonomic and economically advantageous conditions. The effect of high-energy radiation was studied on SBR compounds filled with barite at 50, 75, 100, 125, and 150phr (phr = parts per hundred rubber) of barite concentrations, exposed to ionizing radiation at 0, 100, 200, 500 and 1000kGy doses. The samples were characterized by physic-mechanical tests as rheometry, tensile strength, resilience, hardness, wear resistance, oil absorption, permanent deformation under compression (compression set) and dynamic mechanical thermal analysis. The morphological characteristics were determined by scanning electron microscopy. The results showed that the radiation causes an increase in tensile strength and elongation, the tear strength and hardness, and a decrease in fluid absorção and deformation under compression.